2021
DOI: 10.21203/rs.3.rs-134146/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of future Alzheimer’s disease dementia using plasma phospho-tau combined with other accessible measures

Abstract: A combination of plasma phospho-tau (P-tau) and other accessible biomarkers may provide accurate prediction about the risk of developing Alzheimer’s disease (AD) dementia. We examined this in patients with subjective cognitive decline (SCD) and mild cognitive impairment (MCI) who were consecutively recruited in the BioFINDER study (n=340). The results were validated in SCD/MCI participants in the ADNI study (n=543). Plasma P-tau, plasma Aβ42/Aβ40, plasma neurofilament light, APOE genotype, brief cognitive test… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 23 publications
6
85
1
1
Order By: Relevance
“…38,50 These associations were only observed in individuals with Aβ pathology 51 , which underpins its specificity for AD neuropathological changes. pTau181 also differentiated patients with mild cognitive impairment (MCI) who converted to AD from non-converters 39,44,52 and had better performance than Aβ42/40. 44 Similar results have been observed in non-demented individuals, with high pTau181 associated with higher risk of progressing to AD dementia.…”
Section: Ptau Formsmentioning
confidence: 99%
“…38,50 These associations were only observed in individuals with Aβ pathology 51 , which underpins its specificity for AD neuropathological changes. pTau181 also differentiated patients with mild cognitive impairment (MCI) who converted to AD from non-converters 39,44,52 and had better performance than Aβ42/40. 44 Similar results have been observed in non-demented individuals, with high pTau181 associated with higher risk of progressing to AD dementia.…”
Section: Ptau Formsmentioning
confidence: 99%
“…This was further demonstrated in the time-to-event analyses in which the models with the most data consistently had highest odds ratio between the classes. The observed complementary information of different diagnostic markers has been shown and explored in the literature previously (17) and the performance achieved with all available data marks the maximum accuracy that can be expected from sequential algorithm with fewer variables or time points. However, under certain conditions, a single or very few markers may be sufficient for a definitive diagnosis and it's the objective of sequential neutral zone classifiers to balance misclassification and acquisition costs.…”
Section: Discussionmentioning
confidence: 62%
“…Motivated by a use case of pre-clinical diagnosis of AD-the most frequent cause of severe cognitive decline at old age, we developed a general statistical framework to objectify the selection of sequence and time of diagnostic markers to include in a decision process. As previous studies indicated the benefit of combining multiple, diverse markers (17), cognitive, brain anatomical, and molecular markers were included here. The performance of the non-sequential strategies consistently improved when multiple cross-sectional and multiple longitudinal measurements were combined.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, plasma AD biomarkers represent a more convenient and less invasive alternative to CSF biomarkers. Previous studies showedplasma p-tau181 ( 50 , 51 ), p-tau217 ( 52 , 53 ), and p-tau231 ( 54 ) isoforms can correctly diagnose and predict AD in large studies. However, this is currently a very expensive technology and, unfortunately, it is not available in low and middle-income countries, where million people are living with dementia.”…”
Section: Discussionmentioning
confidence: 99%